Energy Security in ASEAN Region: Its challenges - Mat Sahid E.J.; Ching Sin T.; Chin Hock G. (Institute of Physics Publishing, 2023)
Economics; Energy conservation; Energy management; Energy policy; Environmental technology; Economic growths; Energy demands; Energy imports; Energy requirements; Energy supplies; Energy supply security; Primary energy demand; Southeast Asia; Energy security